Comparative Pathogenicity of United Kingdom Isolates of the Emerging Pathogen Candida auris and Other Key Pathogenic Candida Species - Borman, Andrew M.; Szekely, Adrien; Johnson, Elizabeth M. (mSphere, 2016)
The incidence of invasive candidiasis, which includes candidemia and deep tissue infections, continues to rise and is associated with considerable mortality rates. Candida albicans remains the most common cause of invasive candidiasis, although the prevalence of non- albicans species has increased over recent years. Since its first description in 2009, Candida auris has emerged as a serious nosocomial health risk, with widespread outbreaks in numerous hospitals worldwide. However, despite receiving considerable attention, little is known concerning the pathogenicity of this emerging fungal pathogen. Here, using the Galleria mellonella insect systemic infection model, we show strain-specific differences in the virulence of C. auris , with the most virulent isolates exhibiting pathogenicity comparable to that of C. albicans , which is currently accepted as the most pathogenic member of the genus. Candida auris , first described in 2009, has since emerged as an important, multidrug-resistant, nosocomial agent of candidemia, with large outbreaks reported worldwide and high mortality rates associated with therapeutic failure. The current study employed C. auris isolates from a variety of centers in the United Kingdom to evaluate the pathogenicity of this emerging pathogen compared to that of other common pathogenic yeast species in the invertebrate Galleria mellonella infection model. We showed that C. auris isolates differ in their growth characteristics in vitro , with a proportion of isolates failing to release daughter cells after budding, resulting in the formation of large aggregates of cells that cannot be physically disrupted. Our results also demonstrate strain-specific differences in the behavior of C. auris in G. mellonella , with the aggregate-forming isolates exhibiting significantly less pathogenicity than their nonaggregating counterparts. Importantly, the nonaggregating isolates exhibited pathogenicity comparable to that of C. albicans , which is currently accepted as the most pathogenic member of the genus, despite the fact that C. auris isolates do not produce hyphae and produce only rudimentary pseudohyphae either in vitro or in G. mellonella . IMPORTANCE The incidence of invasive candidiasis, which includes candidemia and deep tissue infections, continues to rise and is associated with considerable mortality rates. Candida albicans remains the most common cause of invasive candidiasis, although the prevalence of non- albicans species has increased over recent years. Since its first description in 2009, Candida auris has emerged as a serious nosocomial health risk, with widespread outbreaks in numerous hospitals worldwide. However, despite receiving considerable attention, little is known concerning the pathogenicity of this emerging fungal pathogen. Here, using the Galleria mellonella insect systemic infection model, we show strain-specific differences in the virulence of C. auris , with the most virulent isolates exhibiting pathogenicity comparable to that of C. albicans , which is currently accepted as the most pathogenic member of the genus.